An ethnographic study of the work cultures of two higher education faculties: reminiscing in tempo - Humphreys, Michael (1999)
The aim of this thesis is to describe and interpret the professional life of academics in two higher education faculties, one in a Turkish university and the other in a UK Institute of Higher Education. This research employs the ‘culture’ metaphor to provide categories, models, and definitions to structure the longitudinal and contextual processes of the ethnography. ‘Jazz’ is also employed as an aesthetic, linking metaphor throughout the thesis, to illuminate the processes of ethnographic research, highlighting particularly, issues of reflexivity, representation, gender, and paradigm incommensurability. Data collection was by semi-structured interviews; participant observations; document analysis; and informal informant conversations. The resultant research account is subjective, socially constructed, interpretive, idiographic and impressionistic. It is constructed through the surfacing of core themes from qualitative data to create an interpretation of the plurivocal chorus of interviewees set against observational and documentary evidence. Both case studies answer the question ‘what is it like to work as an academic in this faculty?’, and are presented as narratives within an inductive theoretical framework. The study also provides a reflexive commentary, in a set of vignettes, where the author's presence within the text is overtly acknowledged and represented by an ‘I’ characterisation. The thesis attempts to extend the limits of organisational ethnography by applying three interpretive readings to the two ethnographic case studies. The readings are intended to enrich the case studies by: directly addressing the issues of researcher ‘presence’ and reflexivity; ‘empiricising’ the Hatch (1993) cultural dynamics model; and providing a ‘power and gender’ theoretical perspective notably under-deployed in the ‘culture’ literature. The thesis produces significant insight into rule-based bureaucracies and higher-education management behaviour, making suggestions for further research in these fields. The main conclusion, is however, methodological and concerns representational strategies within the ethnographic approach to the study of organisations. The thesis argues that, the combination of case studies and interpretive readings, in creating an idiosyncratic, paradigm-bridging representation of the two professional cultures, achieves additional subtle and penetrative organisational insights unavailable to traditional stand-alone ethnographies. The thesis concludes with an invitation to the reader, as a member of the occupational culture of higher education academics, to ‘sit in’ with the band for the last number and use their own improvisational skills and experience, to create a final ‘interpretation of the ‘culture song’